[OP.4A.02] CHANGES IN PERIPHERAL AND CENTRAL BLOOD PRESSURE IN OBESE PATIENTS UNDERGOING BARIATRIC SURGERY. (September 2017) - Oliveras, A.; Granados, A.M.; Vazquez, S.; Sans, L.; Alvarez, S.; Arias, C.; Ho, T.; Benaiges, D.; Fontdevila, L.; Faura, A.; Ramon, J.; Goday, A.; et al.
Abstract : Objective: To assess changes in office and 24h-ambulatory blood pressure (BP), both peripheral- and central-, in obese patients 1 month after bariatric surgery (BxS). Design and method: Prospective study of patients with morbid obesity undergoing BxS. Office-BP (mean of 4 manual measurements) and 24h-ambulatory-BP, both peripheral and central, were measured by the Mobile-O-Graph ® device at baseline and 1 month after BxS. Changes in all BP parameters were evaluated. Results: Thirty-five patients scheduled for BxS (77% women; age: 41.5 ± 9.7yr; body weight: 119 ± 22Kg; hypertensives: 49%) were included and prospectively evaluated. One month after BxS, a significant decrease was observed in all parameters of both peripheral and central (systolic and diastolic) BP, both in office-BP and in the 24 h and in the daytime periods, but not during the nighttime period (Table). These changes occurred in both hypertensive and normotensive patients. Figure. No caption available. Conclusions: In obese patients there is a decrease in both peripheral and central BP in the short-term after bariatric surgery, regardless of the baseline hypertensive state.